Morphology dependence degradation of electro- and magnetoactive poly(3-hydroxybutyrate-co-hydroxyvalerate) for tissue engineering applications - Amaro, Luis (2020)
Poly(hydroxybutyrate-co-hydroxyvalerate) (PHBV) is a piezoelectric biodegradable and biocompatible polymer suitable for tissue engineering applications. The incorporation of magnetostrictive cobalt ferrites (CFO) into PHBV matrix enables the production of magnetically responsive composites, which proved to be effective in the differentiation of a variety of cells and tissues. In this work, PHBV and PHBV with CFO nanoparticles were produced in the form of films, fibers and porous scaffolds and subjected to an experimental program allowing to evaluate the degradation process under biological conditions for a period up to 8 weeks. The morphology, physical, chemical and thermal properties were evaluated, together with the weight loss of the samples during the in vitro degradation assays. No major changes in the mentioned properties were found, thus proving its applicability for tissue engineering applications. Degradation was apparent from week 4 and onwards, leading to the conclusion that the degradation ratio of the material is suitable for a large range of tissue engineering applications. Further, it was found that the degradation of the samples maintain the biocompatibility of the materials for the pristine polymer, but can lead to cytotoxic effects when the magnetic CFO nanoparticles are exposed, being therefore needed, for magnetoactive applications, to substitute them by biocompatible ferrites, such as an iron oxide (Fe3O4).